2017
DOI: 10.1080/0142159x.2017.1324948
|View full text |Cite
|
Sign up to set email alerts
|

Students’ motivation toward feedback-seeking in the clinical workplace

Abstract: In medical education, students are increasingly regarded as active seekers of feedback rather than passive recipients. Previous research showed that in the intentions of students to seek feedback, a learning and performance goal can be distinguished. In this study, we investigated the intentions (defined as level and orientation of motivation) of different performing students (low, average, and high performing students) to seek feedback in the clinical workplace using SelfDetermination Theory. We conducted a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
(13 reference statements)
1
8
0
1
Order By: Relevance
“…SDT predicts that fulfilment increases an individual's sense of self and well‐being, and the pursuit of learning for pure interest, curiosity, challenge and enjoyment: a form of motivation associated with deeper learning, effective performance, and improved psychological health and well‐being. Conversely, the undermining of these constructs leads progressively towards externally regulated, and an eventual lack of, motivation, characterised by apathy and ‘going through the motions’ . The results of this study have informed the continuing discussion with general practices in our area hosting medical students.…”
Section: Discussionmentioning
confidence: 58%
“…SDT predicts that fulfilment increases an individual's sense of self and well‐being, and the pursuit of learning for pure interest, curiosity, challenge and enjoyment: a form of motivation associated with deeper learning, effective performance, and improved psychological health and well‐being. Conversely, the undermining of these constructs leads progressively towards externally regulated, and an eventual lack of, motivation, characterised by apathy and ‘going through the motions’ . The results of this study have informed the continuing discussion with general practices in our area hosting medical students.…”
Section: Discussionmentioning
confidence: 58%
“…Based on the analysis of assessment information, three studies concluded that the approach benefited all learners to maximize their learning, including the students that were initially falling behind [25,31,32]. However, assessors raised concerns that programmatic assessment could be more challenging for learners with a non-native background due to the essential role of narratives [30], and one study reported the influence of learners' performance level on their feedback-seeking behaviour [26]. Although learners perceiving assessment as a decision moment did not necessarily mean it was not beneficial for their learning, studies also showed assessment was commonly perceived as high-stakes or hampering the learning opportunity [17,[20][21][22]33].…”
Section: Theme 1: the Integration Of The Decision-making And Learningmentioning
confidence: 99%
“…instructions, guidelines, consensus meetings) [16,17,22,29,30,34,38,40]. This shared understanding was further impacted by teachers' and learners' personal values and belief systems [21,28,34,35,39]; their previous assessment experience [22,30,33,40]; the level of their experience with programmatic assessment [16, 17, 20-22, 28-30, 33, 34, 38, 40, 41]; and learners' confidence level, motivation, or orientation towards learning [20,21,26,28,33,34,39]. Teachers and learners had to gain trust in and understanding of the system [16,20,22,28,29,33,38,41].…”
Section: Theme 3: the Influence Of Social And Personal Aspects On Assmentioning
confidence: 99%
“…Іншою важливою обставиною є врахування досвіду роботи: мінімуму та максимуму досвіду сумісної роботи учасників освітнього процесу -викладача та слухача [2]. У системі моніторингу якості надання освітніх послуг запровадження зворотного зв'язку зі слухачами має важливе значення [3].…”
Section: вступunclassified